Variations of one computational geometry problem - Skūpienė , Jūratė (Lietuvos matematikos rinkinys, 2004)
It is not an easy task to create a challenging problem for the Olympiads in Informatics. The problem should satisfy many requirements. The paper tries to reveal possible stages of development which lead from the original idea to the final formulation of the problem. The computational geometry task Rectangles, used in Baltic Olympiad in Informatics' 2004 is taken as an example.
Keywords: teaching of informatics; algoritmization; algoritmization methods; informatics olympiads; com¬piutational geometry